Out of the shadows - Ireland, Justina (2021)
"Sylvestri Yarrow is drawn into a squabble between two of the Republic's most powerful families over a patch of space on the frontier. Tangled up in familial politics is the last place Syl wants to be, but the promise of a big payoff is enough to keep her interested ... Meanwhile, Jedi Knight Vernestra Rwoh and her Padawan Imri Cantaros arrive at the capital along with Jedi Master Cohmac Vitus and his Padawan, Reath Silas--and are asked to assist with the property dispute on the frontier. But why? What is so important about an empty patch of space? The answer will lead Vernestra to a new understanding of her abilities, and take Syl back to the past ... and to truths that will finally come out of the shadows"--
Keywords: Jedi (Fictitious characters) -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Life on other planets -- Juvenile fiction; Space warfare -- Juvenile fiction; Science fiction; Young adult fiction